1998
DOI: 10.1007/s004310050786
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary interaction during partial liquid ventilation in surfactant-treated preterm lambs

Abstract: Cardiac output and pulmonary blood flow do not change significantly during PLV and therefore do not appear to contribute to improved gas exchange. This stable cardiac performance occurs at lower wall stress and thereby more advantageous energetic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Data for the effect of PFC on pulmonary vascular and right ventricular pressure are controversial. For total liquid ventilation an increase in pulmonary vascular resistance and thus right ventricular afterload was found, but the results for partial liquid ventilation are less prominent [21,30].…”
Section: Discussionmentioning
confidence: 93%
“…Data for the effect of PFC on pulmonary vascular and right ventricular pressure are controversial. For total liquid ventilation an increase in pulmonary vascular resistance and thus right ventricular afterload was found, but the results for partial liquid ventilation are less prominent [21,30].…”
Section: Discussionmentioning
confidence: 93%
“…With PLV there is the potential for a rise in intrathoracic pressure with the instillation of dense perfluorocarbon liquid into the lungs with an increase in central venous pressure and a decrease in cerebral blood flow, the opposite effect to that seen in this study. Also, PLV is known not to affect central venous pressure once it has been started [20,21] , although this has not been studied during perfluorocarbon liquid dosing. PLV redistributes pulmonary blood flow within the lungs [21] , and the possibility exists that an overall decrease in pulmonary vascular resistance may decrease right atrial pressures, increase cerebral perfusion pressure and increase cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…107,141 During PLV in the premature lamb, lung compliance increased significantly, but left ventricular output, absolute pulmonary blood flow, ductal flow, systemic arterial pressure, heart rate, left ventricular ejection and shortening fraction, and velocity of circumferential fiber shortening remain unchanged, while meridional wall stress was reduced. 142 In vitro study of the isolated perfused neonatal piglet injured lung model demonstrated that PLV reduced or prevented an increase in PVR. 143 These studies suggest that improved gas exchange during PLV is related to enhanced mechanical stability of the lung, which may preserve pulmonary blood flow rather than alter central hemodynamics.…”
Section: Preclinical Studiesmentioning
confidence: 99%